Proceedings of the VII European Congress on Computational Methods in Applied Sciences and Engineering (ECCOMAS Congress 2016) 2016
DOI: 10.7712/100016.2365.10824
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disc Geometry on the Dynamic Stability of Direct Spring Operated Pressure Relief Valves

Abstract: Abstract. The most important parameter of a direct spring operated pressure relief valve is its capacity, which is the rated flow through the valve under conditions given by the corresponding industrial standard. There are several phenomena due to which dynamic instabilities may arise in the system, leading to dangerous oscillations and reduced flow rate. One of the causes of these instabilities is the acoustic coupling of the valve with its upstream piping, the mathematical background of which has already bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In general though, it should be noted that the encapsulation of the exiting flow features into a single discharge coefficient C d for a given fluid and geometry is an engineering simplification. In practice, as can be confirmed with CFD Misra et al (2002); Bazsó and Hős (2012); Erdődi and Hős (2015), the 'coefficient' can be shown to a (typically quite weak) function of the valve opening, C d (x v ), which is relatively straightforward to determine experimentally. We should stress though that variation of C d with x v is not believed to be the primary cause behind any form of valve instability.…”
Section: Valve Mass Flow Ratementioning
confidence: 50%
“…In general though, it should be noted that the encapsulation of the exiting flow features into a single discharge coefficient C d for a given fluid and geometry is an engineering simplification. In practice, as can be confirmed with CFD Misra et al (2002); Bazsó and Hős (2012); Erdődi and Hős (2015), the 'coefficient' can be shown to a (typically quite weak) function of the valve opening, C d (x v ), which is relatively straightforward to determine experimentally. We should stress though that variation of C d with x v is not believed to be the primary cause behind any form of valve instability.…”
Section: Valve Mass Flow Ratementioning
confidence: 50%